854 Melatonin. (17th August 2022) - Mohamed, Ayat; Groves, Caroline
Abstract : UHNM NHS TRUST Aims: Sleep is extremely important to support children's development both physically and mentally. Establishing good sleep patterns can help children to meet their full potential. A good night's sleep can help them to: Maintain a healthy weight, Grow up, Have more energy and Concentrate at school Melatonin is a hormone that occurs naturally in our bodies when it gets dark. Its produced at night time to help us go to sleep. Physiological levels of melatonin and/or melatonin derivates are commonly below average in ASD and correlate with autistic behaviour. Abnormalities in melatonin‐related genes may be a cause of low melatonin levels in ASD. studies reported gene abnormalities that could contribute to decreased melatonin production or adversely affect melatonin receptor function in a percentage of children with ASD. Some children, particularly those with autistic spectrum, are prescribed melatonin to help with their sleep issues. When children have a disturbed sleep cycle, melatonin can help restore a more natural sleep pattern. Melatonin is commonly used for insomnia in children, has a favourable side‐effect profile, is inexpensive and readily available, and is often efficacious for sleep abnormalities Objectives: Analyse available sleep diaries to assess improvement in sleep onset and total time asleep before and after used melatonin. To provide evidence to new medicines committee that Melatonin is important for normal sleep Pattern in children with autism and other developmental disorders. Present information to new medicines committee in liaison with pharmacy Methods: Retrospective observational data collected from March to November 2020 Identified children on melatonin. Used sleep diaries pre/post melatonin, I portal and medisec to collect date. Data collected and analyzed on excel spread sheet. Inclusion Criteria Children with ASD (Autistic Spectrum Disorder), Children with ADHD and Children with sleep problem and learning difficulties. Place: Community Department, Royal stoke University Hospital Sample size: 23 children (19 child with pre/post sleep diary, 4 children with incomplete sleep diary). Results: Two third of children included in the study were males, one third were females. 17 children with ASD, 2 with ADHD and 4 with other learning difficulties. Total sleep hours for ASD patient before melatonin average 6 hours and after melatonin average 9.2 hours. Total sleep hours for all patient before melatonin average 6 hours per day and after melatonin average 9.3 hours/day Total hours to fall asleep after bed time for all patient before melatonin average 2.7 and after melatonin average 1 hour Total hours to fall a sleep after bed time for ASD patients average 3.1 before melatonin and 1 hour after melatonin. Conclusion: Our study showed that Melatonin demonstrates a significant effect on sleep duration and on sleep onset latency compared with both baseline sleep diaries using effect size calculations especially in ASD children. Our Recommendation To continue use the sleep diary pre/post melatonin as standard To present our data to new medicine committee in liaison with pharmacy, in order to allow General Practitioners, prescribe Melatonin